2009
DOI: 10.1001/archoto.2009.143
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Treatment of Late Neck Metastasis in Esthesioneuroblastoma

Abstract: Treatment of neck metastases occurring 6 or more months after an initial diagnosis of ENB with combined surgery and radiotherapy provides a statistically significant survival advantage vs single-modality therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 42 publications
(36 reference statements)
1
49
0
1
Order By: Relevance
“…Esthesioneuroblastoma is a relatively uncommon tumor of the nasal modality treatment of neck metastases demonstrated a statistically significant survival benefit over radiation alone or neck dissection alone [6,12,14]. Salvage of local recurrence has also been studied in patients with esthesioneuroblastoma, but a meta-analysis failed to demonstrate superiority of salvage surgery + radiation over surgery alone or radiation alone for local recurrence [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esthesioneuroblastoma is a relatively uncommon tumor of the nasal modality treatment of neck metastases demonstrated a statistically significant survival benefit over radiation alone or neck dissection alone [6,12,14]. Salvage of local recurrence has also been studied in patients with esthesioneuroblastoma, but a meta-analysis failed to demonstrate superiority of salvage surgery + radiation over surgery alone or radiation alone for local recurrence [15].…”
Section: Discussionmentioning
confidence: 99%
“…Positive surgical margins, advanced Kadish or T stage, and cervical or distant metastases are correlated with decreased survival. Studies have shown that patients with cervical metastasis can benefit from salvage with neck dissection and post-operative neck irradiation [12]. In patients requiring skull base resection a multilayer repair of the skull base, preferably with a vascularized flap such as the nasoseptal flap, decreases the risk of postoperative CSF leak [13].…”
Section: Case Reportmentioning
confidence: 99%
“…However, in several different reviews and metaanalyses of the largest and most recent series the overall rate of synchronous and metachronous cervical metastases is reported to be between 20.2% and 23.4% [26][27][28][29]. Gore et al [28] state that 62% of cervical metastases occur 6 or more months after primary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gore et al [28] state that 62% of cervical metastases occur 6 or more months after primary treatment. Moreover, the presence of such metastases is usually related to the development of distant metastases and poor prognosis, in general [26,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation